Occult carcinoma in an adult choledochal cyst. Issue 784 (February 1991) - Dowsett, J. F.; Rode, J.; Chandiramani, V. A.; Russell, R. C.
Abstract : The complications of choledochal cyst are avoidable if diagnosed early, and adequate resection undertaken. This case report describes the long history of right subcostal pain in a young man of 26 who had a squamous carcinoma in a choledochal cyst diagnosed after serial section of the excised cyst. Subsequent resection of the head of the pancreas showed histological residual tumour from which he died 4 months later. This case illustrates the need for complete early excision of a choledochal cyst to prevent this complication.